2009
DOI: 10.1080/08820130902832035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the CCR5-Δ32 Mutation on Hepatitis C Virus-Specific Immune Responses in Patients with Haemophilia

Abstract: In hepatitis C virus (HCV) infection antiviral T cells express the CC chemokine receptor 5 (CCR5). Their recruitment to the liver is an important step in the immune response. A 32 base pair deletion in the CCR5 gene leads to reduced expression and total loss of CCR5 in CCR5-Delta32 heterozygous and homozygous subjects, respectively. However, the role of this mutation for antiviral immunity remains unclear. Here, we analysed proliferation, IFN-gamma and IL-4 secretion (ELISpot) induced by the HCV antigens core,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…[8] However, HCV-specific immune responses may be impaired by the CCR5 delta-32 mutation as well. [9] Wald et al . suggested that the CCR5 delta-32 allele may be associated with decreased hepatic inflammation in HCV-infected patients using histopathologic outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…[8] However, HCV-specific immune responses may be impaired by the CCR5 delta-32 mutation as well. [9] Wald et al . suggested that the CCR5 delta-32 allele may be associated with decreased hepatic inflammation in HCV-infected patients using histopathologic outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, mice lacking CCR5 showed impaired macrophage function and reduced efficiency to clear Listeria monozytogenes infection [51]. However, in humans, immune dysfunction associated with the CCR5D32 mutation is rather subtle in T lymphocytes but seems to involve HCV-specific interferon-gamma production [52]. Beyond that, the CCR5 receptor is critically involved in hepatic recruitment of immuno-competent cells, including dendritic cells (DC).…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines and chemokine receptors have been shown to be critically involved in these processes (20) and CCR5Δ32 bpdel carriers of HCV positive patients (as presented in the current study) remain poor clearance during the HCV therapy by the masking of some other related genotypes (20, 21). Ahlenstiel et al have claimed that point mutation in CCR5-Delta32 interrupts the CCR5 signalling pathway due to may potentially result in subtle reduction of HCV specific IFN-gamma responses in anti-HCV-positive haemophiliac patients (22). The current limited results and some other recent literature findings support the above hypotheses (23-26).…”
Section: Discussionmentioning
confidence: 99%